Gold-catalyzed cycloisomerization of pyridine-bridged 1,8-Diynes: An expedient access to luminescent cycl[3.2.2]azines - Chintawar, Chetan C.; Mane, Manoj V.; Tathe, Akash G.; Biswas, Suprakash; Patil, Nitin T. (Organic Letters, 2019)
Gold-catalyzed diyne cycloisomerizations involving carbene/alkyne metathesis have been the focal point of attention for the past few years as it offers great potential to build complex polycyclic architectures. However, the design of novel cycloisomerizations has been mostly limited to 1,5/1,6-diynes and has remained very challenging to apply for higher 1,n-diynes. Herein, we disclose an unprecedented cycloisomerization of pyridine-bridged 1,8-diynes involving carbene/alkyne metathesis to access luminescent cycl[3.2.2]azines.